Habilidades sociais e ansiedade social na infância e Adolescência: correlações e comparações entre grupos - Nobre, Mirella Rodrigues (2019)
Social Skills consists on a set of social behaviors that can be developed and presented by individuals through their interpersonal relationships. These skills may suffer some influence by the environment through culture and society. A deficit in acquiring and performing these skills may occur when faced with a context that does not naturally favor learning. Social Skills deficits are considered risk factors for psychosocial functioning and are associated with psychological disorders. The literature indicates, as in several empirical researches, that Social Anxiety Disorder is related to deficits on social skills repertoires. Taking that correlation into account and also considering the importance of studies that discuss the theme to assist in the treatment of this disorder, the present research aimed to verify the connection between specific social skills and Social Anxiety Disorder indicators in middle school students from two public schools in the city of Maceió – AL. A total of 191 students aged 10 to 13 years old, properly registered in the schools where the research took part, participated in the study. The instruments used in this research were the Behavior Problems and Academic Competence for Children (SSRS) and the Social Phobia Inventory (SPIN – Social Phobia Inventory). The results indicated that more than half of the participants showed Social Anxiety symptoms (55.4%). Two groups were created: one group with participants that showed social anxiety symptoms and another one without. That division established a database for correlation and comparison analysis. The correlation analysis between social anxiety and social skills evaluated by children, both for a general sample as for the group with social anxiety indicators, demonstrated that the higher the anxiety, the lower the frequency of empathy behaviors. In the teachers evaluation were found that the highest degree of social anxiety, lower the frequency of behaviors related to affectivity and cooperativeness. The comparison of the social skills repertoire evaluated by the children between groups with or without social anxiety indicated that there were only differences between the degrees of responsibility, demonstrating that children without social anxiety indicators are less responsible. In the teacher‘s evaluation, there were no significant differences between groups. These results were discussed in terms of social skills resources and deficits in children that present Social Anxiety. There is also significant importance of future studies that can evaluate the degrees of predictions on specific social skills in social anxiety, aiming to assist in evaluating processes and social skills training in that context.